Pelaksanaan penyeliaan pengajaran dan motivasi kerja guru di Sekolah Menengah Kebangsaan Negeri Selangor / Ahmad Kamal Ariffin - Ahmad Kamal, Ariffin (2016)
The purpose of this research was to determine the level of instructional supervision implementation in national secondary schools, the main criteria of successful instructional supervision, factors that affect the successfulness of the instructional supervision implementation and to identify the significant relationship between instructional supervision and teachers’ motivation. The conceptual framework of this research was developed by combinating of two conseptual frameworks, Behavioral Process Model for Instructional Supervision Teachers (Lovell, 1978) and Operating System Model by Stoner and Wankel (1985). To collect data, Quan-qual methods were used by distributing questionnaires to 1,646 teachers in 40 national secondary schools in Selangor. The qualitative method using interview involved 24 teachers of four national secondary schools in Selangor. The data was analysed using discriptive statistics such as mean score, standard deviation, an independent –t test, one-way Analysis of Variance (ANOVA), Post Hoc Scheffe and multiple regression analysis. The main findings of the research showed that all the five dimensions i.e. an implementation of training programme, management of teaching environment, management of curricular programme, implementation of reporting the programme and implementation of rewards for teachers were the factors that significantly affected the success of instructional supervision implementation and hence, affected the teachers’ motivation. However, all the demographic factors tested under this research did not significantly affect the success of the instructional supervision implementation and teachers’ motivation. The research implication suggested that the Ministry of Education is supposed to strengthen the instructional supervision program particularly in the areas of reporting the program and rewarding the teachers.